Social Economic Development Strategy: Problems, Priorities, Decisions - Melnikas, Borisas (Ekonomika, 2001)
The main problems and priorities of the preparing and realization of the long-term modernization and development strategies in the East - and Central European counties, especially in Lithuania, are exposed.The methods and problems of strategic decisions making are described.The phenomenons of globalization, international integration and information societies development as the main factors of the modernization and social, economic and technological development in the East - and Central European countries, especially in Lithuania, are analyzed.Some ideas of long-term social economic strategy for Lithuania are discussed.